Paradoxes in O. Wilde’s “The Picture of Dorian Gray” - Dalalyan, Manana; Mkrtchyan, Hasmik (Armenian Folia Anglistika, 2013)
One of the underlying functions of any piece of literary work is its aesthetic impact on the reader. The Picture of Dorian Gray by O. Wilde has completely fulfilled its aesthetic mission from the 19th century onwards. The ideological basis of the novel heavily rests upon paradoxes which make the speech of the author and his attitude to the external world and its established traditions more impressive. Paradox is also an aesthetic category which is expressed through contrasts, juxtaposition, parallel constructions, descending gradation. Sometimes the same phrase can be viewed from the perspective of several means of expression.